Gambaran Swamedikasi Pada Mahasiswa di Indonesia - Angga Dwi Prasetyo (Program Studi S1 Farmasi, STIKES Senior, Medan, 2023)
Self-medication can be interpreted as the treatment of all diseases that exist within oneself through simple medicines. Someone who uses self-medication when